2018
DOI: 10.3892/mmr.2018.8813
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone/microRNA‑141/FOXA2: A novel axis in pancreatic β‑cells proliferation and insulin secretion

Abstract: MicroRNAs (miRs) are considered to be effective, post‑transcriptional regulators in the pathophysiology of type 2 diabetes (T2D) and promising treatment targets. However, the function of miR‑141 remains to be elucidated. In the present study, upregulation of miR‑141 was demonstrated in diabetic mice and elderly diabetic patients. Using reverse transcriptase‑quantitative polymerase chain reaction, luciferase reporter assays and western blotting, forkhead box A2 (FOXA2) was identified as a direct target gene of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Additionally, miR-34a was shown to contribute to lipotoxicity in palmitic or stearic acid-induced ␤-cell injury (25). Furthermore, an increased level of miR-141 can result in impaired glucose-stimulated insulin secretion in diabetic mice and elderly diabetic patients (47). miR-297, which often acts as a tumor suppressor, has been implicated in various physiological and pathological conditions, such as carcinoma (43,49), meiosis (44), and cardiac hypertrophy (3,50).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miR-34a was shown to contribute to lipotoxicity in palmitic or stearic acid-induced ␤-cell injury (25). Furthermore, an increased level of miR-141 can result in impaired glucose-stimulated insulin secretion in diabetic mice and elderly diabetic patients (47). miR-297, which often acts as a tumor suppressor, has been implicated in various physiological and pathological conditions, such as carcinoma (43,49), meiosis (44), and cardiac hypertrophy (3,50).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] Glucose-induced DNA methylation in the promoter region and miRNAs such as miR-141, miR-124a, and miR-342 inhibit FOXA2 expression in pancreatic β cells. [28][29][30] In pancreatic α cells, memin interacts with FOXA2 to repress its transcriptional activity. 31 In the islets of type 2 diabetic animals and humans, nuclear FOXA2 distribution was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor forkhead box protein A2 (FOXA2), also known as hepatocyte nuclear factor 3‐beta (HNF‐3β), is also critical for maintaining pancreatic cell functions by regulating PDX1 expression . Glucose‐induced DNA methylation in the promoter region and miRNAs such as miR‐141, miR‐124a, and miR‐342 inhibit FOXA2 expression in pancreatic β cells . In pancreatic α cells, memin interacts with FOXA2 to repress its transcriptional activity .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there should be a role for miR-200 in EMT. Upregulation of miR-141 has been demonstrated in IR, as well as in EC [169,170,196]. The increased expression of miR-141 resulted in impaired glucose-stimulated insulin secretion and pancreatic β-cell proliferation.…”
Section: Mirnas In Both Insulin Resistance and Endometrial Cancermentioning
confidence: 99%
“…In addition, a positive correlation was observed in diabetic patients between miR-141 expression and blood glucose concentration. Forkhead box A2 (FOXA2) was identified as a direct miR-141 target gene [170]. Separate work demonstrated that FOXA2 must be important in tumorigenesis based on its role in the inhibition of EMT in cancer [203,204].…”
Section: Mirnas In Both Insulin Resistance and Endometrial Cancermentioning
confidence: 99%